Effect of trypsin concentration on living SMCC‐7721 cells studied by atomic force microscopy. (13th August 2021) - Yan, Jin; Xie, Chenchen; Zhu, Jiajing; Song, Zhengxun; Wang, Zuobin; Li, Li
Abstract: Trypsin is playing an important role in the processes of cancer proliferation, invasion and metastasis which require the precise information of morphology and mechanical properties on the nano‐scale for the related research. In this work, living human hepatoma (SMCC‐7721) cells were treated with different concentrations of trypsin solution. The morphology and mechanical properties of the cells were measured via atomic force microscope (AFM). Statistical analyses of measurement data indicated that with the increase of trypsin concentration, the average cell height and the surface roughness were both increased, but the cell viability, the cell surface adhesion and the elasticity modulus were decreased significantly. The force required to puncture the cells was also gradually reduced. It indicates that trypsin not only hydrolyses the proteins between the cell and the substrate but also the membrane proteins. The results offer valuable clues for the cancerous process study, pathological analysis and trypsin inhibitor drug development. And this work provides an effective way for overcoming the cell membrane in drug injection for cell‐targeted therapy.